Seismic testing of post-tensioned Pres-Lam core walls using cross laminated timber. (15th July 2018) - Moroder, Daniel; Smith, Tobias; Dunbar, Andrew; Pampanin, Stefano; Buchanan, Andrew
Highlights: First ever experimental testing of a post-tensioned timber core wall structure. Under SLS loads, wall panels can be assumed to be connected rigidly to each other. Supplementary dissipative devices provide stable hysteretic energy dissipation. Clamping forces from the PT prevent sliding between panels and at the foundation. Displacement incompatibilities can be accommodated by simple connections details. Abstract: With the increasing demand for multi-storey timber buildings in areas with high wind loads and high seismic activity, stiff lateral load resisting systems are becoming a crucial design component. Post-tensioned Pres-Lam mass timber lift shafts and stairwell core walls not only provide a strong and very stiff lateral load resisting system, but also damage limiting response in the case of a large seismic event. This paper describes the results of experimental tests on Cross-Laminated Timber (CLT) Pres-Lam core walls tested under bi-directional quasi-static seismic loading. In the first configuration the CLT wall panels were connected in the corners with screws, while in the second configuration, steel pivotal columns were introduced at the corners and the CLT wall panels were connected to the steel columns with dissipative U-shaped Flexural Plates (UFPs). Overall the testing showed that the Pres-Lam system, when used for structural timber core walls subjected to bidirectional loading regimes, sustains nominal damage after large drift demands. By adding ductile screw-connections or steel columns with UFPs at the corners additional strength and dissipation capacity is obtained. Friction between the CLT panels improved the seismic performance of the structure, which in Serviceability Limit State (SLS) conditions led to rigid behaviour of the splices between the panels. Displacement incompatibilities between the floor diaphragm and the core walls were accommodated by locating the connections at the centre of the walls, or by pinned connections in the corner pivotal columns. Relative displacements between orthogonally running connector beams were accommodated by using flexible connections out-of-plane. Under low axial forces there was horizontal sliding of the walls at the foundation level, but this was not observed when larger post-tensioning forces were applied.